Interesting symbols on some deniers tournois of Naupaktos - Bontas, Andrei (KOINON: The International Journal of Classical Numismatic Studies, 2022)
The coinage of Naupaktos (Nepanto/Lepanto in contemporary sources) for Philip de Taranto as despot of Romania (and from c. October 1304 Prince of Achaea) was a large-scale operation that lasted for a few years at the beginning of the 14th century (c. 1301-1306). The mint city of Naupaktos had a complex situation as a point of contention between Angevin interests and the Greek Epirote faction represented by Thomas Komnenos Doukas, the direct male heir of despot Nikephoros of Epiros, and his regent mother Anna Palaiologina Kantakouzene. Philip, married to Thamar, daughter of Nikephoros and Anna and sister of Thomas, was in line to receive the city at the death of his father-in-law (c. 1297) but his claim was countered by Anna and Thomas and a succession conflict ensued, in which Naupaktos changed hands a few times. In between this uncertainty, Philip was likely holding the city from ca. 1300 to mid 1305 and/or again by the winter of 1305-6, when the mint was still producing coinage. This is the time when the denier was minted here, possibly at first in very small quantities for Thomas d’Autrementcourt, Lord of Salona, and then the large emissions for Philip as Despot of Romania. The opening of an Angevin mint at Naupaktos might have also been prompted by the non-approved wedding between Isabelle de Villehardouin and Philip of Savoy, which put the mint at Clarentza outside the control of the Angevins in 1301.